2011
DOI: 10.1371/journal.pone.0022352
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Trade-Off between Starvation and Predation Risks in Ducks

Abstract: The theory of trade-off between starvation and predation risks predicts a decrease in body mass in order to improve flight performance when facing high predation risk. To date, this trade-off has mainly been validated in passerines, birds that store limited body reserves for short-term use. In the largest avian species in which the trade-off has been investigated (the mallard, Anas platyrhynchos), the slope of the relationship between mass and flight performance was steeper in proportion to lean body mass than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…In addition, parameters such as traffic density and traffic noise are likely to be associated with speed limit, so that the detected effect of speed limit might in fact be owing to combined effects of average car speed, traffic density and noise intensity. A better understanding of the mechanisms responsible for our results would require either experiments in more controlled conditions [21] or the consideration of a large number of species with known territory size and mobility. Response to humans and associated mortality risk is considered a major issue for bird conservation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, parameters such as traffic density and traffic noise are likely to be associated with speed limit, so that the detected effect of speed limit might in fact be owing to combined effects of average car speed, traffic density and noise intensity. A better understanding of the mechanisms responsible for our results would require either experiments in more controlled conditions [21] or the consideration of a large number of species with known territory size and mobility. Response to humans and associated mortality risk is considered a major issue for bird conservation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that birds must balance the benefits of maintaining low body mass to facilitate escape from predators with the reduced risk of starvation that results from increased fuel supplies. The increase in body mass that occurs in the absence of predators (Gosler et al, 1995) and the decrease in body mass in response to an increase in the perceived risk of predation (Gentle and Gosler, 2001; Zimmer et al, 2010, 2011) support this hypothesis. However, empirical data supporting a link between flight performance and WL is equivocal.…”
Section: Introductionmentioning
confidence: 90%
“…Empirical data on escape and flight behaviour has often supported these assumptions (Metcalfe and Ure, 1995;Kullberg et al, 1996;Lees et al, 2014;Van Den Hout et al, 2010;Nudds and Bryant, 2002;Lind et al, 1999); however, results that contradict these assumptions have also been reported (Kullberg, 1998;van der Veen and Lindström, 2000;Jones et al, 2009;Macleod, 2006;Dierschke, 2003). Empirical studies of changes in fat storage under changes in predation pressure largely support the idea that fat storage is reduced when predation pressure (or perceived predation pressure) increases (Gosler et al, 1995;Cresswell, 1998;Rogers, 2015;Pascual and Carlos Senar, 2015;Zimmer et al, 2011;MacLeod et al, 2007;Cimprich and Moore, 2006;Macleod et al, 2005a,b;Ydenberg et al, 2004;Pérez-Tris et al, 2004;Piersma et al, 2003;Gentle and Gosler, 2001;van der Veen, 1999;Carrascal and Polo, 1999;Fransson and Weber, 1997;Pravosudov and Grubb, 1998;Rogers, 1987;Witter et al, 1994; but see Lilliendahl 1997Lilliendahl , 1998. However, studies of birds killed by predators do not indicate that fatter birds are killed more frequently (Sullivan, 1989;Whitfield et al, 1999;Møller and Erritzøe, 2000;Genovart et al, 2010); indeed, some studies suggest that leaner birds are more prone to predation risk (Dierschke, 2003...…”
Section: Set-point Theorymentioning
confidence: 96%